Identifying substitutional oxygen as a prolific point defect in monolayer transition metal dichalcogenides - Barja, Sara; Refaely-Abramson, Sivan; Schuler, Bruno; Qiu, Diana Y.; Pulkin, Artem; Wickenburg, Sebastian; Ryu, Hyejin; Ugeda, Miguel M.; Kastl, Christoph; Chen, Christopher; Hwang, Choongyu; Schwartzberg, Adam; et al. (Nature Publishing Group, 2019)
Chalcogen vacancies are generally considered to be the most common point defects in transition metal dichalcogenide (TMD) semiconductors because of their low formation energy in vacuum and their frequent observation in transmission electron microscopy studies. Consequently, unexpected optical, transport, and catalytic properties in 2D-TMDs have been attributed to in-gap states associated with chalcogen vacancies, even in the absence of direct experimental evidence. Here, we combine low-temperature non-contact atomic force microscopy, scanning tunneling microscopy and spectroscopy, and state-of-the-art ab initio density functional theory and GW calculations to determine both the atomic structure and electronic properties of an abundant chalcogen-site point defect common to MoSe2 and WS2 monolayers grown by molecular beam epitaxy and chemical vapor deposition, respectively. Surprisingly, we observe no in-gap states. Our results strongly suggest that the common chalcogen defects in the described 2D-TMD semiconductors, measured in vacuum environment after gentle annealing, are oxygen substitutional defects, rather than vacancies.